Ultraviolet and visible micro‐Raman and micro‐photoluminescence spectroscopy investigations of stress on a 75‐mm GaN‐on‐diamond wafer. Issue 8 (22nd February 2017) - Hancock, B. Logan; Nazari, Mohammed; Anderson, Jonathan; Piner, Edwin; Faili, Firooz; Oh, Seajin; Francis, Daniel; Twitchen, Daniel; Graham, Samuel; Holtz, Mark W.
Abstract : Investigations of stress distributions and material quality across a 75‐mm wafer consisting of device‐quality GaN integrated with a diamond substrate are presented. Stress in the GaN are mapped both over the full wafer and across the layer along the growth direction. Ultraviolet (UV) and visible micro‐Raman and UV photoluminescence (PL) spectroscopy from both sides of the wafer reveal an unexpected gradient between the tensile stress at the free GaN surface (∼0.86–0.90 GPa) and the GaN/diamond interface (∼0.05–0.23 GPa). The stresses obtained exhibit good cross‐wafer uniformity. The stress gradient is understood through variations in the material along the growth direction of the layers due to the presence of threading dislocations which result in local stress relaxation. Transmission electron microscopy confirms the presence of extended defects to be greater near the interface with diamond, corresponding to the initial GaN growth regime, and diminished toward the surface where transistors would be fabricated in a full device technology. Finite element (FE) simulations describing the observed stress dependence along with TEM imaging of the GaN cross‐section support the relaxation interpretation.